2017
DOI: 10.1186/s13075-017-1473-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased synovial lipodystrophy induced by high fat diet aggravates synovitis in experimental osteoarthritis

Abstract: BackgroundMetabolic syndrome (MetS) may be associated with knee osteoarthritis (OA), but the association between the individual components and OA are not well-understood. We aimed to study the effect of hypercholesterolemia on synovial inflammation in knee OA.MethodsOA was surgically induced in rabbits fed with standard diet (OA group, n = 10) or in rabbits fed with high fat diet (OA-HFD, n = 10). Healthy rabbits receiving standard diet (Control, n = 10) or fed with HFD (HFD, n = 6) were also monitored. Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…These suggested that leptin was necessary in the development and progression of obesity-related OA. In contrast, a recent study reported inconsistent findings showing that leptin gene expression was markedly decreased in the synovial membrane in the rabbits with OA 62 . Adipose tissue may affect the metabolism of joint tissues through secretion of adipokines, leading to the pathological changes in knee OA.…”
Section: Mechanisms Underlying the Link Between Adipose Tissue And Knmentioning
confidence: 86%
“…These suggested that leptin was necessary in the development and progression of obesity-related OA. In contrast, a recent study reported inconsistent findings showing that leptin gene expression was markedly decreased in the synovial membrane in the rabbits with OA 62 . Adipose tissue may affect the metabolism of joint tissues through secretion of adipokines, leading to the pathological changes in knee OA.…”
Section: Mechanisms Underlying the Link Between Adipose Tissue And Knmentioning
confidence: 86%
“…This highlights the importance of M1 macrophage subsets in the development of obesity-associated OA ( 57 ). Furthermore, HFD aggravates synovial inflammation during OA, by increasing macrophage infiltration and metabolic-mediated remodeling of adipose tissue, together with a significant presence of pro-inflammatory factors ( 58 ). Additionally, free fatty acids induce activation of Toll-like receptor 2 (TLR2) or TLR4, trigger macrophage recruitment, and activate the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome ( 59 ).…”
Section: Metainflammation In Oamentioning
confidence: 99%
“…Rabbits were kept in individual transparent 50 × 40 × 40 cm cages that allow social interactions. After 2 weeks of acclimatization with ad-libitum access to water and standard commercial chow, rabbits were randomly separated into four groups (20).…”
Section: Experimental Model In Rabbitsmentioning
confidence: 99%
“…Since rabbits have been claimed as the best animal model for lipid-related research (17,18), we employed rabbits with normal cholesterol metabolism in our study, in order to analyse the effect of high fat diet (HFD) on OA progression. Furthermore, we carried out an experimental model of high lipid intake that is not associated to an increase in weight gain, that allows to adequately address the contribution of added mechanical load and hyperlipidaemia in cartilage alterations (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%